Risk of primary Sjogren’s Syndrome following human papillomavirus infections: a nationwide population-based cohort study - Chen, Huang-Hsi; Ma, Kevin Sheng-Kai; Dong, Chen; Chang, Wen-Jung; Gao, Kuan-Rong; Perng, Wuu-Tsun; Huang, Jing-Yang; Wei, James Cheng-Chung (Frontiers in Immunology, 2022)
Introduction Viral infection is an exogeneous factor for primary Sjogren’s syndrome (pSS). This study investigated the association between human papillomavirus (HPV) infections and pSS through analysis in a nationwide, population-based cohort study. Methods Patients with HPV infections between January, 1999 and December, 2013 were included. The incidence of new-onset pSS in patients with HPV infections and non-HPV controls were derived. The multiple Cox regression model derived the risk of pSS in patients with HPV infections. Subgroup analysis and sensitivity analysis were performed to validate the association. Results The follow-up period was nearly 12 years. The adjusted hazard ratio (aHR) of pSS in the HPV cohort was significantly higher than the non-HPV cohort (aHR=1.64, 95% CI=1.47-1.83, P<0.001). The risk of pSS increased with age and the risk increased by 2.64-fold (95% CI= 2.37-2.93) for the group older than 45 years. Females had 2.78 times the risk of males (95% CI= 2.5-3.125). The significant association between HPV and the risk of pSS persisted in the sensitivity analysis restricted in HPV infections that lasted over 12 months (aHR=1.63, 95%CI=1.45-1.83, P<0.0001). Subgroup analyses revealed that both male (aHR=1.83, 95%CI=1.47-2.28, P<0.0001) and female (aHR=1.58, 95%CI=1.40-1.79, P<0.0001) patients with HPV infections and HPV-infected patients aged between 16 and 45 years (aHR=1.60, 95%CI=1.34-1.91, P<0.0001) and over 45 years (aHR=1.67, 95%CI=1.46-1.91, P<0.0001) have significantly greater risk of pSS. Conclusion Patients with HPV infections presented with a significantly higher risk of pSS, regardless of age and sex